The Association Between Mobile Game Addiction and Depression, Social Anxiety, and Loneliness - Jin-Liang Wang; Jia-Rong Sheng; Hai-Zhen Wang (Frontiers in Public Health, 2019)
As a new type of addictive behaviors and distinct from traditional internet game addiction on desktop computers, mobile game addiction has attracted researchers' attention due to its possible negative effects on mental health issues. However, very few studies have particularly examined the relationship between mobile game addiction and mental health outcomes, due to a lack of specified instrument for measuring this new type of behavioral addiction. In this study, we examined the relationship between mobile game addition and social anxiety, depression, and loneliness among adolescents. We found that mobile game addiction was positively associated with social anxiety, depression, and loneliness. A further analysis on gender difference in the paths from mobile game addiction to these mental health outcomes was examined, and results revealed that male adolescents tend to report more social anxiety when they use mobile game addictively. We also discussed limitations and implications for mental health practice.